2013
DOI: 10.1186/1471-2369-14-4
|View full text |Cite
|
Sign up to set email alerts
|

High serum bicarbonate level within the normal range prevents the progression of chronic kidney disease in elderly chronic kidney disease patients

Abstract: BackgroundMetabolic acidosis leads to chronic kidney disease (CKD) progression. The guidelines recommend a lower limit of serum bicarbonate level, but no upper limit. For serum bicarbonate level to be clinically useful as a therapeutic target marker, it is necessary to investigate the target serum bicarbonate level within the normal range to prevent CKD progression.MethodsOne hundred and thirteen elderly CKD patients, whose serum bicarbonate level was controlled within the normal range, were enrolled in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…The optimal management of metabolic acidosis in chronic kidney disease patients including the monitoring or administration of bicarbonate has not been established yet. [1][2][3] However various guidelines have recommended serum bicarbonate levels to be maintained at or above twenty two mleq/ltr bicarbonate replacement therapy in On Dialysis 62%…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal management of metabolic acidosis in chronic kidney disease patients including the monitoring or administration of bicarbonate has not been established yet. [1][2][3] However various guidelines have recommended serum bicarbonate levels to be maintained at or above twenty two mleq/ltr bicarbonate replacement therapy in On Dialysis 62%…”
Section: Discussionmentioning
confidence: 99%
“…The approximate prevalence of CKD in India is 800 per million population. 1 Prevalence of CKD patients will continue to rise, reflecting the growing elderly population and increasing number of patients with diabetes and hypertension. 1,2 Metabolic acidosis is a feature of CKD due to the reduced capacity of the kidney to synthesize ammonia and excrete hydrogen ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(41) have shown that the maintenance of serum bicarbonate at high-normal levels reduced CKD progression and increased patient survival. Reduction of protein catabolism and the hospitalization rate were also reported (24,42,43). KDIGO consensus (1) establishes that patients with CKD and serum bicarbonate < 22 mmol/L require oral bicarbonate replacement.…”
Section: Ckd-mbd Managementmentioning
confidence: 99%
“…A systematic review concluded that the studies were suggestive but not definitive for a beneficial effect, with little indication of significant adverse effects (16). In addition, some observational studies are consistent with a beneficial effect of a higher bicarbonate (or lower acid intake) on CKD progression (17)(18)(19)(20).…”
mentioning
confidence: 99%